Current tendencies of judicial review as reflected in the new Hungarian Code of Administrative court procedure - Rozsnyai, Krisztina (Central European Public Administration Review, 2019)
The continuing expansion of judicial review of administrative actions, as seen throughout Europe, led to the engulfment of the administrative ju- diciary towards the end of the last century. Review within a reasonable timeframe is hard to grant for this reason: the tensions between lawful- ness and efficiency are amplified. The answers given to alleviate this ten - sion raise questions that lie at the heart of the system of checks and ba- lances between public administration and the judiciary. This article aims to present some of respective tendencies. To concretise these tenden- cies, the article analyses some relevant solutions given by the very new code of administrative court procedures, the Hungarian Act No. I of 2017. The most important elements of the regulation of procedures for judicial review of administrative action are provided in a dogmatic and a compa- rative perspective showing the changes of rules and/or their interpreta- tion through the judiciary. Thus, major challenges regarding the present understanding of the doctrine of separation of powers are emphasised. The most significant elements of the new Hungarian regulation are pre - sented in a coherent system, which also gives insight on the codificational considerations. Legislation and jurisprudence must deal with the highli- ghted aspects in any national and in EU legal systems alike.
Keywords: administrativni postopek; Madžarska; pravo; upravni sodni postopek; začasna pomoč